Application of elemental fingerprinting for the authentication of tea: A review - Agustina Ari Murti Budi Hastuti&, Abdul Rohman& (Journal of Applied Pharmaceutical Science, 2022)
Tea is one of the most popular beverages in the world. Some tea products are highly sought after and have higher commercial value. As a result, the authentication of tea is of importance and is frequently addressed in current literature. Multielemental determination with the aid of multivariate data analysis has been successfully performed to determine the authenticity of tea. We conducted a literature review on existing methods that applied elemental fingerprinting for tea authentication. We systematically searched the electronic database Web of Science for literature over the last two decades. The elemental determinations for tea authentication were performed using inductively coupled plasma-mass spectrometry, inductively coupled plasma-optical emission spectroscopy, atomic absorption spectroscopy, X-ray fluorescence, and/or laser-induced breakdown spectroscopy. Principal component analysis, linear discriminant analysis, and artificial neural network were among the most frequently used multivariate data analysis techniques. The elemental fingerprinting technique appears to be a promising source of information for categorizing tea based on geographical origins, harvesting time, cultivars, and types.
Keywords: Tea, elemental fingerprinting, chemometrics, provenance, authentication